Analisis Kerentanan Sosial Ekonomi Petani Nilam di Desa Kombungo Kecamatan Lasalepa Kabupaten Muna - Selfina, Selfina; Alwi, La Ode; Rianse, Ilma Sarimustaqiyma (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This study aims to determine the socio-economic vulnerability of patchouli farmers in Kombungo Village, Lasalepa District, Muna Regency. Determination of the study sample was carried out in a census. Using data analysis methods and techniques s income analysis coring. The results of the study found social vulnerability in Kombungo Village in the category is very vulnerable to the period of education6-7.8 as many as 26 people or 43.33% farmers with a score of 1, the category of very not vulnerable has an education period of 13.6-15.4 as many as 5 people or 8.33% with a score of 5, and health parameters in the very category not vulnerable to the frequency of treatment 1.2-0 with a total of 56 people or 93.33 % with a score of 5 , a category very susceptible to the frequency of treatment from 6.4 to 5.2 with the number of 1 person or 1.67% with a score of 1. The economic vulnerability in Kombungo Village in the vulnerable category is Rp.15,489,800-26,369,100 with a total of 18 people or 30% with a score of 2, the category is very not vulnerable, Rp.48,130,700-59,010,000 with a total of 7 or 11.67% with a score of 5.